Garantía Mobiliaria sobre Créditos - Mejorada Chauca, Martin (2015)
In this article, author makes a description and analysis of the performance of security interest in credits. in that sense, it is analys the credit as object of security interest. Also, it is analyze the particular process of the creation of this security interest and its opposability to third parties. Finally, there is the process of execution of the foregoing security interest.